2022
DOI: 10.1111/hae.14624
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of free‐living physical activity measurements between ActiGraph GT3X‐BT and Fitbit Charge 3 in young people with haemophilia

Abstract: Introduction: Measurement of physical activity (PA) using commercial activity trackers such as Fitbit devices has become increasingly popular, also for people with haemophilia (PWH). The accuracy of the Fitbit model Charge 3 has not yet been examined. Aims: To compare the Fitbit Charge 3 against the research-grade accelerometer Acti-Graph GT3X-BT in measuring average daily steps and minutes spent in different PA intensities.Methods: Twenty-four young PWH wore a wrist-worn Fitbit Charge 3 and hip-worn ActiGraph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
(131 reference statements)
1
12
0
Order By: Relevance
“…It seems reasonable to conclude therefore that the two devices do not agree well for both steps and MVPA minutes, except for days where there were few steps/MVPA minutes. This is similar to the findings of Matlary et al 12 who found for the Fitbit Charge 3 there was a mean of 3388 more steps and 18 more MVPA minutes compared to the ActiGraph, with an increasing difference with a greater number of steps/MVPA minutes.…”
Section: Matlary Et Al Trackers Were Worn On Their Non-dominant Wrist...supporting
confidence: 90%
See 1 more Smart Citation
“…It seems reasonable to conclude therefore that the two devices do not agree well for both steps and MVPA minutes, except for days where there were few steps/MVPA minutes. This is similar to the findings of Matlary et al 12 who found for the Fitbit Charge 3 there was a mean of 3388 more steps and 18 more MVPA minutes compared to the ActiGraph, with an increasing difference with a greater number of steps/MVPA minutes.…”
Section: Matlary Et Al Trackers Were Worn On Their Non-dominant Wrist...supporting
confidence: 90%
“…ActiGraphs were initialised to a sampling frequency of 30 Hz. 12 Data was extracted for each participant from their Fitbit account dashboard and Garmin connect app.…”
Section: Matlary Et Al Trackers Were Worn On Their Non-dominant Wrist...mentioning
confidence: 99%
“…34 In this study, the mean daily step counts over seven consecutive days for ActiGraph and Fitbit in adults with haemophilia were 7349 and 10,924 steps, respectively. 34 Nevertheless, we observed similar Fitbit step counts compared to our finding at the 1-year follow-up, suggesting the accuracy of the measures in the same cohort. In this context, Fitbit could be a good tool to promote long-term PA self-monitoring and encourage patient adherence to daily PA goals but not for comparison with normative values.…”
Section: (B)mentioning
confidence: 58%
“…The current study also has some limitations. We acknowledge that Fitbit overestimation of PA estimates 16 may be a source of bias when comparing our results to studies using different devices. In addition, we do not know whether wear time was the same in the two groups.…”
Section: Discussionmentioning
confidence: 90%
“…We found moderate to high correlations between Fitbit and Acti-Graph GT3X measured daily averages for all PA variables, but the Fitbit tended to overestimate steps and minutes in light and vigorous intensity PA. 16 However, the ActiGraph is not a criterion measure for PA measurement, and its limitations include that is does not capture non-ambulatory activities well, and inability to capture the extra energy expenditure associated with for example carrying loads or walking uphill. 10 Furthermore, wear-compliance is often lower for hipworn than wrist-worn devices.…”
Section: Introductionmentioning
confidence: 99%